CFD simulations of heat transfer enhancement using Al2O3–air nanofluid flows in the annulus region between two long concentric cylinders - Saad Aldossary; Anas Sakout; Mouhammad El Hassan (Energy Reports, 2022)
The heat transfer enhancement of the flow in the annulus region between two concentric long horizontal cylinders is of a great importance in many industrial cooling applications such as those utilizing heat exchangers for removal of waste heat. In this study, Computational Fluid Dynamics (CFD) is employed to investigate the natural convective heat transfer of laminar flows with and without suspending nanoparticles of synthetic alumina (Al2O3) in air (base fluid). The effects of the Knudsen number (Kn), Rayleigh number (Ra) or modified Rayleigh number (Ram), annulus gap spacing size between the two cylinders (Aspect Ratio: AR), and the volume fraction (φ) of the solid alumina nanoparticles on the radial heat transfer are investigated. The ranges of these physical parameters considered in this work are as follows: 0.01 ≤ Kn ≤ 0.1, 103 ≤ Ra ≤ 105 matching with 0.63 ≤ Ram ≤ 2, and 0% ≤φ≤ 4% covering a range of Prandtl number (Pr) of 0.01 ≤ Pr ≤ 0.97 over an annulus gap spacing of AR = 1. To solve the coupled set of governing equations, a finite volume simulation is applied taking into consideration the buoyancy effect using Boussinesq approximation. Over the ranges of physical parameters considered in this study, it is found that a significant enhancement in heat transfer rates is obtained by suspending 1% of alumina nanoparticles (φ=1%). It is also noticed that a negligible increase in heat transfer is obtained for φ > 4% and the same conclusion is observed for Ra > 104 over the investigated range of φ. It is observed that the heat transfer (average Nusselt number, Nu) increases as Kn number decreases (AR, φ, and Ram are constant).